Acute Intermittent Porphyria: Expanding our differential diagnosis - Fernández-Narváez, Carlos Geraldo (2020)
A 24 year-old woman with a history of severe and recurrent abdominal pain, neuropsychiatric manifestations and who developed rapid and progressive quadriparesia. Having ruled out other entities, the values of porfobilinogen and uroporphyrins in urine were elevated. She was treated with 10% dextrose solutions and complications management.